2022
DOI: 10.14348/molcells.2021.0204
|View full text |Cite
|
Sign up to set email alerts
|

Rich Phase Separation Behavior of Biomolecules

Abstract: Phase separation is a thermodynamic process leading to the formation of compositionally distinct phases. For the past few years, numerous works have shown that biomolecular phase separation serves as biogenesis mechanisms of diverse intracellular condensates, and aberrant phase transitions are associated with disease states such as neurodegenerative diseases and cancers. Condensates exhibit rich phase behaviors including multiphase internal structuring, noise buffering, and compositional tunability. Recent stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 100 publications
(129 reference statements)
0
16
0
Order By: Relevance
“…53 Aberrant phase separation was demonstrated as a contributing factor to the pathogenesis of neurodegenerative diseases and cancer. 34,35 However, the roles of LLPS in cardiovascular diseases remain poorly understood. Here, we reported that the mechanoreceptive protein DDR1 is capable of undergoing LLPS in response to collagen binding or ECM stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Aberrant phase separation was demonstrated as a contributing factor to the pathogenesis of neurodegenerative diseases and cancer. 34,35 However, the roles of LLPS in cardiovascular diseases remain poorly understood. Here, we reported that the mechanoreceptive protein DDR1 is capable of undergoing LLPS in response to collagen binding or ECM stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Recently, LLPS was indicated to play a vital role in human health and diseases. 34,35 There is little information as to how LLPS is involved in vascular physiology and pathophysiology. Here, we describe an LLPS-dependent mechanism of DDR1 mediating Hippo-dependent YAP activation in response to the mechanical and chemical stimuli.…”
mentioning
confidence: 99%
“…LLPS occurs within cells as macromolecules transition between dense and diluted phases, which is necessary for achieving the lowest free energy state [ 10 ]. A characteristic of LLPS is the presence of threshold concentrations of macromolecules, which are affected by several biophysical parameters, including temperature, salt concentration, and ions [ 6 ].…”
Section: Biological Characteristics Of Llpsmentioning
confidence: 99%
“…Like the liquid phase, when the temperature changes, it may separate into two immiscible liquid phases, or into a solid phase and a liquid phase. LLPS refers to the phenomenon in which two mixed liquids are separated from each other ( 38 40 ). Phase separation can be coupled with various other phase transitions in the complex environment in vivo , which physically range from non-viscous (like water at room temperature) to gel-like.…”
Section: The Multivalent Interactions Between Biological Macromolecul...mentioning
confidence: 99%